Results of standardized government tests: an educational quality indicator - Barragán, Sandra; Marcelo, Eliacid (Frontiers in Education, 2023)
Considering the advances of standardized government assessments and their impact on the quality of education around the world, the aim of this paper was to characterize the influence of the results of the Saber 11 standardized test on Colombian public policies and on the quality of education, especially in Bogotá, from 2012 to 2022. To achieve this objective, a non-experimental methodology was designed using a mixed descriptive approach and a documentary source. Following the two phases of the methodology, the public policies, the characteristics of the test, the students assessed, the assessors, and the results for Bogotá were described. When achieving the proposed characterization, the discrepancy between the results of those evaluated and the goals proposed in the government plans was also observed. This discrepancy has not subsided despite the evolution of related public policies. The results of standardized government tests for Bogotá were better than in the rest of the country, without implying that they are good. The national average and the average of the global scores for Bogotá were very close to half of the possible score to obtain. The results of the English tests placed Bogotá in the lower part of the scale in the Common European Framework.